2005
DOI: 10.1111/j.1365-2141.2005.05834.x
|View full text |Cite
|
Sign up to set email alerts
|

Red blood cells, platelets and polymorphonuclear neutrophils of patients with sickle cell disease exhibit oxidative stress that can be ameliorated by antioxidants

Abstract: Summary Sickle cell disease (SCD) is basically a red blood cell (RBC) disorder characterised by sickling and haemolysis, but platelets and polymorphonuclear neutrophils (PMN) are also involved. Oxidative damage may play a role in the pathogenesis of SCD. Using flow cytometry, we measured oxidative‐state markers simultaneously in RBC, platelets and PMN obtained from 25 normal donors, nine homozygous (SS) patients and six SS/beta‐thalassaemia patients. Reactive oxygen species (ROS) and reduced glutathione (GSH) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
132
1
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(141 citation statements)
references
References 35 publications
(51 reference statements)
5
132
1
3
Order By: Relevance
“…The tumorigenic effect of iron has been attributed to several factors, such as overproduction of ROS and free radicals through irondependent Fenton reaction, induction of oxidative responsive transcriptional factors and pro-inflammatory cytokines and iron-mediated hypoxia signaling [39][40][41][42]. Consistent with previous studies [43,44], we demonstrated that iron treatment (FAC 32 μM, similar to the mean iron concentration in our breast cancer patients) could induce about 1.9-fold increase of intracellular ROS level in MBA-MB-231 cells compared to the control (Fig. 8A, P b 0.001), while DFO significantly reduced ROS generation (Fig.…”
Section: Iron and Il-6 Jointly Promoted Tumor Cell Growthsupporting
confidence: 80%
“…The tumorigenic effect of iron has been attributed to several factors, such as overproduction of ROS and free radicals through irondependent Fenton reaction, induction of oxidative responsive transcriptional factors and pro-inflammatory cytokines and iron-mediated hypoxia signaling [39][40][41][42]. Consistent with previous studies [43,44], we demonstrated that iron treatment (FAC 32 μM, similar to the mean iron concentration in our breast cancer patients) could induce about 1.9-fold increase of intracellular ROS level in MBA-MB-231 cells compared to the control (Fig. 8A, P b 0.001), while DFO significantly reduced ROS generation (Fig.…”
Section: Iron and Il-6 Jointly Promoted Tumor Cell Growthsupporting
confidence: 80%
“…The oxidative stress of erythrocytes accompanies many pathological conditions, such as sickle cell and iron deficiency anemias and thalassemia [8,29,30], as well as aging [17,31], hypoxia [9] and obesity [32]. An intensive search has been going on for natural antioxidants to treat diseases induced by RONS.…”
Section: Discussionmentioning
confidence: 99%
“…Increased amounts of oxidizing molecules, such as ROS, are produced during periods of reperfusion (Dhalla et al, 2000;Klings & Farber, 2001) and when neutrophils become activated or adhere to the endothelium (Mohamed et al, 1993;Hofstra et al, 1996). Previous studies have shown a 10-to 30-fold higher ROS production in red bld cells, platelets and polymorphonuclear neutrophils from SCD patients, compared with their normal counterparts (Amer et al, 2006). Signals transduced by adhesion molecules play a critical role in ROS production by eosinophils (Chihara et al, 1995).…”
Section: Altered Functional Properties Of Eosinophils In Sickle Cell mentioning
confidence: 99%